Hubungan Aktivitas Fisik dengan Status Gizi Remaja Usia Sekolah Menengah Pertama - Sofiani, Eva Kurnia; Rahayu, Mita Vera Pujiani; Senia, Erlina; Luakusa, Asti Rinike; Lestari, Catur Retno (Indonesian Journal of Nutrition Science and Food, 2024)
Nutritional status in adolescents is influenced by several factors, one of which is physical activity. Physical activity is any body movement that can increase energy expenditure so as to prevent the body from experiencing obesity. Poor physical activity in adolescents can give the possibility of undernutrition or overnutrition. The purpose of this study was to determine the relationship between physical activity and nutritional status of adolescents of junior high school age. This study is descriptive analytic with cross sectional design with a student population of SMP N 2 Karangrayung totaling 804 students. The research sample was conducted using purposive sampling method where a sample of 30 students was obtained. Data collection was carried out by distributing IPAQ-SF questionnaires which were distributed using google form, measuring nutritional status based on age (BMI / U). Data analysis using the SPSS 29 program with chi-square test to determine the relationship between physical activity and nutritional status. Based on the results of the study, 40.0% of students had light physical activity and 60.0% of students had moderate physical activity. The most nutritional status was dominated by respondents with normal nutritional status (60.0%) and for the least undernutrition (6.7%) and the rest had more nutritional status (33.3%). The results of the study found a significant relationship (p-value 0.045) between physical activity and nutritional status in students of SMP N 2 Karangrayung.